The mathematical learning by Mathcad software use - Petraitienė, Stasė; Bikulčienė, Liepa; Kravčenkienė, Violeta (Lietuvos matematikos rinkinys, 2002)
The usidge of special mathematical software are impossible without mathematical knowledge, because they use functions which is common in everyday use. The MathConnex convert data from Excel, Matlab to MathCad and other way.